Improved Particle Spray Algorithm for Modeling Globular Cluster Streams - Yingtian Chen; Monica Valluri; Oleg Y. Gnedin; Neil Ash (The Astrophysical Journal Supplement Series)
Stellar streams that emerge from globular clusters (GCs) are thin stellar structures spread along the orbits of progenitor clusters. Numerical modeling of these streams is essential for understanding their interaction with the host galaxy's mass distribution. Traditional methods are either computationally expensive or oversimplified, motivating us to develop a fast and accurate approach using a particle spray algorithm. By conducting a series of N -body simulations of GCs orbiting a host galaxy, we find that the position and velocity distributions of newly escaped stream particles are consistent across various GC masses and orbital parameters. Based on these distributions, we develop a new algorithm that avoids computing the detailed internal cluster dynamics by directly drawing tracer particles from these distributions. This algorithm correctly reproduces the action space distribution of stream particles and achieves a 10% accuracy in stream morphology and velocities compared to N -body simulations. To facilitate broader use, we have implemented this algorithm in galactic dynamics codes agama , gala , galax , and galpy .